SEKOLAH MENENGAH PERTAMA INKLUSI DI KOTA PONTIANAK - Aulia Mustika Ratu; Muhammad Ridha Alhamdani; Rudiyono Rudiyono (JMARS: Jurnal Mosaik Arsitektur, 2021)
Indonesia is a country that pays attention to the education of its young generation. The school education unit plays a very important role in the education of children. Indonesia already has a program in the form of Child-Friendly Districts/Cities (KLA). KLA is a district/city with a development system that guarantees the fulfillment of children's rights and special protection for children that is carried out in a planned, comprehensive, and sustainable manner to achieve Child-friendly Indonesia (IDOLA) which is expected to be achieved in 2030. Pontianak city crowned as a Child Friendly City (KLA) at the first level since 2017 which subsequently up to become Madya. In this regard, the Pontianak City Government runs the Child Friendly School program as effort to realize the fulfillment of children's rights and protection for 8 hours of children being in school, and also the aim of being a forum that facilitates equitable educational needs for all children, both those with special needs, and with disabilities that presented in the form of Inclusive Junior High Schools. The Inclusive School design method used the idea stage, the data collection stage, the analysis stage, the synthesis stage, and the design stage. The program used in the design of the Inclusive Junior High School is the Child-Friendly School (SRA). The result is a child-friendly inclusive school design by applying the philosophy of “Behind Weaknesses There Are Advantages”. This is indicated by the facilities that accommodate activities in schools, both macro, and micro.